Deteksi Vibrasi Pada Pesawat Tanpa Awak Berbasis Arduino Uno Dalam Mendukung Pertahanan Udara - Eca Indah Anggraini; Asep Adang Supriyadi; Yahya Darmawan (Journal on Education, 2024)
Rapid advances in technology have penetrated various sectors. One of these related to air defense system using hexacopter-type unmanned aircraft. When airborne, hexacopter must maintain balance through rotation of propeller. Therefore, vibration level detection system needed on hexacopter. In this research, direct data processing approach used on microcontroller using FFT method. Fourier algorithm used to convert continuous into discrete signals, while sensor system built using MPU 6050 sensor. Sensor testing carried out by analyzing its characteristics, as well as comparing results of data processing directly and indirectly. Results obtained were in stationary conditions, accelerometer values for x, y, and z axes did not contain any anomalies, indicating that there was no vibration. In floating condition, there are no anomalous values in accelerometer axes x and z values, while on y axis there are anomalous values at frequency of 100-200Hz which indicates presence of vibration. In flying conditions, there are no anomalous values in z-axis accelerometer value, while on x and y axes there are anomalous values at frequency of 100-500Hz which indicates presence of vibration. So, it can be concluded that vibration detection of accelerometer on x, y and z axes using the MPU 6050 sensor can detect vibrations well